A new species of Coryogalops (Perciformes: Gobiidae) and the first adult record of Feia nympha from the Red Sea - Kovačić, Marcelo; Bogorodsky, Sergey V.; Mal, Ahmad O. (Zootaxa, 2016)
A new species of the gobiid genus Coryogalops, C. nanus sp. nov. is described from the Red Sea. Coryogalops nanus sp. nov. is distinguished from congeners in having dorsal-fin rays VI + I,10; anal-fin rays I,9; pectoral-fin rays 12−14 (lowest count known for the genus), two upper rays with free tips; pelvic fins I,5, joined to form an emarginate disc, no pelvic frenum; predorsal area and narrow area at base of first dorsal fin naked; longitudinal scale series 26−29; transverse scale rows counted forward 6−7; transverse scale rows counted backward 7−8; circumpeduncular scale rows 11−12; seven transverse suborbital rows of sensory papillae; no tentacle above upper eye margin; anterior nostril tubular, without flap at its tip, posterior nostril pore-like; body semitranslucent, covered with small scattered orange-yellow spots and speckles, those in predorsal area contain black dots; an internal row of white spots along ventral part of body above anal-fin base and on caudal peduncle; head with small scattered orange to yellowish brown spots; first dorsal fin with two broad white bands at base of fin and distally, and with hyaline area densely dotted with melanophores in the middle of fin; preserved specimens opaque white to yellowish with sparse melanophores. An adult specimen of Feia nympha is recorded for the first time in the Red Sea and the lateral line system of this species is described.